Dimension of ownership structure, risk-taking behaviour and performance of non-financial firms in gulf cooperation council countries - Almuqren, Mohammed Khalid S. (2018)
Empirical evidences on the influence of ownership structure on firm performance are not only inexhaustible, there are contradictions that give rise to growing concerns for further studies using an integrated framework that include latent variables to best explain the observed unclear relationship. This paper examined dimensions of ownership structure and firm performance with risk-taking behaviour or level as a moderating variable. Data were drawn from 280 listed non-financial firms in GCC over a ten-year (10) years (2008 – 2017) period, giving 2,520 observations. Ownership structure studied were government, managerial, family, foreign and concentrated ownership in relation to three performance measures namely priceearnings ratio (PERATIO), return on asset (ROA) and operating income (OPINC). Results reveal that government and foreign ownership structures have a significant positive effect on price-earnings ratio, and operating income and not ROA. Managerial ownership also has a significant positive effect on price-earnings ratio and operating income but a significant negative effect on ROA. Family ownership has only a significant positive effect on price-earnings ratio. Ownership concentration has a significant negative effect on price-earnings ratio, and operating income but no effect on ROA. Further, higher risk-taking in firms with government and concentrated ownership significantly improved price-earnings ratio and operating income. Managerial and family ownership improved only ROA and PER respectively, while foreign ownership led to reduction in PER and ROA. Finally, firms in manufacturing do not significantly improved, on average all performance measures except price-earnings ratio than non-manufacturing firms with three of the forms of ownership structure. The study concludes that ownership structure, on average leads to positive effect on performance of non-financial institutions in GCC. Also, risk-taking level, on average, moderates the relationship between ownership structure and performance of non-financial firms in GCC. This means that more risk taking leads to more returns for GCC firms. Nevertheless, manufacturing firms do not perform better except in price-earnings ratio than non-manufacturing firms in GCC region. Practically, drift toward government, foreign or managerial ownership structure could become an ideal movement as these forms of ownership structure contribute to improving performance measures. Firms with concentrated ownership, government, family and managerial ownership could take higher risk for higher returns. Therefore, management could embark on re-rationalizing and re-distributing ownership percentages among government, management or foreign ownership especially in non-manufacturing sector. This way, high market valuation (priceearnings ratio) and efficiency (operating income) could be achieved.